Sociale ongelijkheden in de kans op slagen aan de universiteit. Academische prestaties vanuit het oogpunt van de leefomstandigheden als student - Joël Girès (Brussels Studies, 2024)
The aim of this article is to document the current reality of inequalities in university education, focusing on the way in which purely material difficulties condition the academic performance of students. The statistical analysis is based on survey data collected at Université libre de Bruxelles (ULB); it has the particularity of starting from the living situation of students and categorising them according to the hardships they experience. The survey was carried out during the COVID-19 pandemic, highlighting the difficulties of those in the most precarious situations and thus shedding light on the question of living conditions. The analysis shows that there are indeed significant academic inequalities between students according to their living conditions: the greater the hardship, the lower the students' marks. Students who experience the greatest hardships are more likely to come from modest backgrounds, but we can see that hardship can exist independently of social and family background, indicating that material constraints are an obstacle in themselves to the successful completion of higher education. The analysis also reveals that there are many inequalities with respect to university education, which stem from different social relationships: in particular, at equal social levels, ethno-racial inequalities exist.